Trade Unions and NGOs in Malaysia: Contentions and Collaboration in Organizing Migrant Domestic Workers - Viajar, Verna Dinah Q. (Philippine Journal of Labor and Industrial Relations, 2023)
Domestic work remains vastly perceived as non-work in many countries in Asia, including Malaysia. Excluded and unrecognized in labor laws, migrant domestic workers (MDWs) become invisible from protection against human rights abuses; thus, trade unions (TUs) become constrained to represent domestic workers as well as to organize them. The increasing reports of human rights abuses against MDWs led the attempt of Malaysian TUs and non-government organizations (NGO) to organize domestic workers for many years. The NGOs in Malaysia with concerns as human rights, migrants, women, and religious groups initially addressed the problems and conditions of domestic workers. However, TUNGO relations remain an important factor in differentiating the organizing strategies of NGOs and TUs in responding to domestic workers issues. As the study includes labor-oriented NGOs and non-TU organizations such as self-organized workers as part of the broader labor movement, I intend to show in this discussion, through empirical data, the areas of tensions and spaces for collaboration that exist among these groups in Malaysia. This article discusses the contentious and collaborative relations of civil society groups with the established TUs in Malaysia using the Gramscian notion of establishing hegemony among allied social forces in civil society and establishing linkages between civil society and political society.